From childhood trauma to adult dissociation: the role of PTSD and alexithymia - Terock, Jan; Barnow, Sven (Psychopathology, 2016)
Background: The mechanism of how childhood trauma leads to increased risk for adult dissociation is not sufficiently understood. We sought to investigate the predicting effects and the putatively mediating roles of PTSD and alexithymia on the path from childhood trauma to adult dissociation. Methods: A total of 666 day-clinic outpatients were administered the Childhood Trauma Questionnaire (CTQ), the Toronto Alexithymia Scale (TAS-20), the Posttraumatic Diagnostic Scale (PDS), and the Dissociative Experiences Scale (DES) and controlled for sex, age, and the Global Symptom Index (GSI). Linear regression analyses and mediation analyses were applied. Results: Independent predictive effects on dissociation were found for childhood trauma, alexithymia and PDS, even after adjusting for GSI. Effects of childhood neglect on dissociation were slightly stronger than of abuse. Alexithymia did not mediate the path from childhood trauma to dissociation. Mediation by PDS was specific for childhood abuse, with all PTSD symptom clusters being significantly involved. Conclusions: Childhood abuse and neglect are important predictors of dissociation. While the effects of abuse are mediated by PTSD, the mechanism of how neglect leads to dissociation remains unclear. The results further support the predictive value of alexithymia for adult dissociation above and beyond the effects of childhood trauma, PTSD, and GSI scores.
Gesehen am 21.12.2016